Introducing Ecotourism to Florida's Counties and Landowners: An Ecotourism/Nature Based Tourism Fact Sheet - Miriam S. Wyman; Taylor V. Stein (EDIS, 2007)
FOR-110, a 5-page illustrated fact sheet by Miriam S. Wyman and Taylor V. Stein, defines eco- and nature-based tourism, provides statistics, and discusses positive and negative aspects, community planning, and describes some successful examples. Includes references. Published by the UF School of Forest Resources and Conservation, April 2007.